Enzymatic dehalogenation of pentachlorophenol by extracts from Arthrobacter sp. strain ATCC 33790. - Schenk, T (1989)
Arthrobacter sp. strain ATCC 33790 was grown with pentachlorophenol (PCP) as the sole source of carbon and energy. Crude extracts, which were prepared by disruption of the bacteria with a French pressure cell, showed no dehalogenating activity with PCP as the substrate. After sucrose density ultracentrifugation of the crude extract at 145,000 x g, various layers were found in the gradient. One yellow layer showed enzymatic conversion of PCP. One chloride ion was released per molecule of PCP. The product of the enzymatic conversion was tetrachlorohydroquinone. NADPH and oxygen were essential for this reaction. EDTA stimulated the enzymatic activity by 67%. The optimum pH for the enzyme activity was 7.5, and the temperature optimum was 25 degrees C. Enzymatic activity was also detected with 2,4,5-trichlorophenol, 2,3,4-trichlorophenol, 2,4,6-trichlorophenol, and 2,3,4,5-tetrachlorophenol as substrates, whereas 3,4,5-trichlorophenol, 2,4-dichlorophenol, 3,4-dichlorophenol, and 4-chlorophenol did not serve as substrates.